2005
DOI: 10.1007/s00436-005-0065-z
|View full text |Cite
|
Sign up to set email alerts
|

Giardia lamblia behavior under cytochalasins treatment

Abstract: Giardia lamblia, a flagellated protist, is the parasite most commonly found in the intestinal tract of humans and other mammals causing a disease known as giardiasis. This parasite presents several cytoskeletal structures whose major components are microtubules, namely: the ventral adhesive disk, eight flagella axonemes, the median body, and funis. However, the cytoskeletal filamentous structures are poorly understood, and therefore, less studied. In the present work, we used actin-interacting drugs such as cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
2
13
1
Order By: Relevance
“…S2). We observed filamentous actin structures within Giardia, and in contrast to previous studies using heterologous antibodies of unknown specificity (19,20), we did not observe pronounced actin staining of the ventral disk, a microtubule structure used for parasite attachment.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…S2). We observed filamentous actin structures within Giardia, and in contrast to previous studies using heterologous antibodies of unknown specificity (19,20), we did not observe pronounced actin staining of the ventral disk, a microtubule structure used for parasite attachment.…”
Section: Resultscontrasting
confidence: 99%
“…Cytochalasin and latrunculin have been used previously to probe actin function in Giardia often with conflicting results; moreover, in those studies, either no attempt was made to monitor actin distribution during the experiment, or heterologous antibodies (without controls) or phalloidin were used (20,26, reviewed in ref. 8).…”
Section: Resultsmentioning
confidence: 99%
“…In Giardia , actin was thought to function only in the attachment to glass and cell surfaces, but recently, this protein has been implicated in morphology and cytokinesis [46][49]. Likewise, other reports demonstrated the importance of microfilament integrity for regulated endocytic flow and for recycling of molecules to the plasma membrane [25].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the actin depolymerizing agent cytochalasin D was associated with detachment after 24 hours of exposure [19][21]. Here, iso-osmotic addition of cytochalasin D (0.1 mM) to Giardia growth medium had no significant effect on attachment after three minutes of exposure (Figure 2C).…”
Section: Resultsmentioning
confidence: 49%
“…Short-timescale detachment of Giardia has not been examined in the numerous studies of forced detachment, as most assays measure population attachment levels after a period of 2−24 hours incubation with a given drug or medium composition (e.g. [19][21],[23]). Such studies have shown that Giardia attachment and survival rates are inhibited by changes in pH and osmolality [23], but the long incubation prior to quantification of attachment makes it very difficult to separate direct effects on attachment from an overall effect on cell viability.…”
Section: Discussionmentioning
confidence: 99%